Video-Assisted Thoracoscopic Lung Biopsy as a Possible Cause of Acute Interstitial Pneumonia in a Patient with Nonspecific Interstitial Pneumonia - D Jeffrey Moore; Colm P McParland; Martin J Bullock; Yannick Cartier; Paul Hernandez (Canadian Respiratory Journal)
The present case report describes a 44-year-old woman who presented with dyspnea due to diffuse interstitial lung disease. High-resolution computed tomography showed features of usual interstitial pneumonia, but the lung biopsy obtained by video-assisted thoracoscopy was consistent with a histological pattern of nonspecific interstitial pneumonia. Following the procedure, the patient developed progressive respiratory distress and died on postoperative day 13 with a clinical picture of acute interstitial pneumonia. The autopsy showed evidence of diffuse alveolar damage superimposed on the background pattern of nonspecific interstitial pneumonia. The present case report supports the notion that patients with a variety of subtypes of idiopathic interstitial pneumonias may be at risk of exacerbation of their underlying disease following thoracic procedures, including video-assisted thoracoscopic lung biopsy.